Environment-Based Horticulture Learning: The Effect of Fertilizer Usage Variation on Students’ Environmental Literacy - Eka Trisianawati; Novi Nurmayanti; Ninda Permasari (Didaktika: Jurnal Kependidikan, 2025)
This study investigates the influence of various fertilizer types—NPK, organic, granulated, and block compost—on students’ environmental literacy within an environment-based horticulture learning context. The research aims to determine whether fertilizer-based practical activities contribute to measurable improvements in students’ environmental literacy. A quantitative approach was employed by comparing students’ environmental literacy levels before and after participating in horticultural practicum activities. Data were collected using standardized questionnaires and assessment instruments designed to evaluate environmental literacy. The improvement scores were analyzed using the N-Gain technique, and an independent sample t-test was conducted to assess the significance of the observed differences.The results show an average pre-practicum score of 55, which increased to 74 following the practicum. The independent sample t-test produced a significance value of 0.000, which is lower than 0.05. This indicates that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted, demonstrating that the fertilizer-based practicum had a significant impact on students’ environmental literacy. The findings suggest that integrating diverse fertilizer applications into horticulture learning can effectively enhance students’ environmental literacy. This supports the use of environment-based, hands-on learning strategies as a pedagogical approach for fostering environmental awareness and responsible behavior among students.